Gender perspectives of rice farmers’ livelihood strategies in time of climate change: The case of Ndop plains, Cameroon - Ntam, Fidelis; Malaa, Dorothy (Africa Rice Center, 2023)
A study on livelihood strategies of rice farmers in this time of climate change from a gender perspective was carried out in Ndop, Cameroon. The study characterized local climate conditions and the impact on rice production. It assessed farmers’ perceptions of the changing climate and its effects on their livelihoods. It highlighted constraints and coping strategies to ensure sustainable livelihoods. Participatory rural appraisal tools were used to collect information. Participants were men and women who had resided within the communities for over 20 years. A household survey was used to collect information on gender roles, climate change and rice production. In each village, 10 households were selected randomly: each having two respondents, a knowledgeable male and a knowledgeable female. A total of 60 households and 120 respondents were selected for the study. Both qualitative and quantitative tools were used to analyze the data. The results show that men and women perceive climate change and its consequences differently. The main impact on rice production is low yields and food insecurity. Rice production as well as that of other crops dropped between 40% and 70% during stressed years. The effect of rainfall on rice production was very significant for the period evaluated. Although the resilient communities have used various coping measures, they were not primarily targeted for reducing the impact of climate change. Although indigenous adaptive and mitigation strategies exist, better policy measure to combat climate change are desperately needed because the study showed that the smallholders are unprepared for the environmental disasters which accompany climate change.